RELIGION IN THE CRITICAL DECADES - Brynaichi, Javan Al (Journal of Dharma, 1996)
That the next few decades are critical to the survival and wellbeing of our race is becoming increasingly obvious. Those of us who are held in the compulsive understanding of religious conviction will regard spiritual awareness as vital: Our race must rise in spirit, or fall to death. First consider the problems that close in on us, which may form the first basis of agreement between all who become aware, whether we regard ourselves as theistic or atheistic, pragmatic or idealistic.